REKONSEPTUALISASI DIKLAT GURU DALAM PENGEMBANGAN PROFESIONAL BERKELANJUTAN: ANALISIS LITERATUR - Pardiyawan Pardiyawan; Sugiantoro Sugiantoro; Mukti Ali; Muhammad Afdal; Khaeruddin Khaeruddin; Irnie Victorynie (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Continuing professional development for teachers is currently experiencing a paradigm shift from traditional models to more personalized and collaborative learning. This study aims to systematically synthesize international literature on the reconceptualization of teacher education and training (CPD) over the past ten years. Using a systematic literature review (SLR) method strictly guided by the PRISMA framework, researchers analyzed 20 high-quality articles from the Scopus database for the period 2015-2025. The analysis results show a fluctuating but increasing trend in publication growth, dominated by the social sciences (56.3%) and primarily focused on the digital transformation of post-pandemic education. Quantitative data revealed that technology integration was the most influential theme, with the most cited articles reaching 47 times. Methodologically, quantitative approaches dominated up to 60% of all reviewed studies. The findings identified that practice-based models, professional learning communities (PLCs), and mentoring have proven effective in improving pedagogical competence. However, the sustainability of CPD is strongly influenced by the interaction of individual intrinsic motivation, school leadership support, and the availability of adequate supporting infrastructure. The main conclusion emphasizes the need to reconceptualize training design from an episodic-technocratic approach to an adaptive, contextual, and long-term professional learning ecosystem. This systemic strategy is crucial for bridging national policy reforms with real-world classroom practice, ensuring that teacher professional development significantly impacts the quality of student learning.ABSTRAK Pengembangan profesional berkelanjutan bagi guru saat ini mengalami pergeseran paradigma dari model tradisional ke arah pembelajaran yang lebih personal dan kolaboratif. Penelitian ini bertujuan untuk mensintesis secara sistematis literatur internasional mengenai rekonseptualisasi pendidikan dan pelatihan guru (CPD) dalam sepuluh tahun terakhir. Dengan menerapkan metode systematic literature review (SLR) yang dipandu secara ketat oleh kerangka kerja PRISMA, peneliti menganalisis 20 artikel berkualitas tinggi dari basis data Scopus periode 2015-2025. Hasil analisis menunjukkan tren pertumbuhan publikasi yang fluktuatif namun cenderung meningkat, didominasi oleh bidang ilmu sosial (56,3%) dan fokus utama pada transformasi digital pendidikan pascapandemi. Data kuantitatif mengungkapkan bahwa tema integrasi teknologi merupakan yang paling berpengaruh, dengan artikel tersitasi tertinggi mencapai 47 kali. Secara metodologis, pendekatan kuantitatif mendominasi hingga 60% dari keseluruhan studi yang diulas. Temuan mengidentifikasi bahwa model berbasis praktik, komunitas belajar profesional (PLC), serta mentoring terbukti efektif meningkatkan kompetensi pedagogik. Namun, keberlanjutan CPD sangat dipengaruhi oleh interaksi motivasi intrinsik individu, dukungan kepemimpinan sekolah, dan ketersediaan infrastruktur pendukung yang memadai. Simpulan utama menegaskan perlunya rekonseptualisasi desain diklat dari yang bersifat episodik-teknokratis menuju ekosistem pembelajaran profesional yang adaptif, kontekstual, dan berorientasi jangka panjang. Strategi sistemik ini sangat krusial untuk menjembatani reformasi kebijakan nasional dengan praktik nyata di dalam kelas guna memastikan pengembangan profesional guru berdampak signifikan pada kualitas belajar peserta didik.